2022
DOI: 10.3390/ijms23095153
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Growth, Oxidative Injury and Chloroplast Ultrastructure in Leaves of Lolium perenne and Festuca arundinacea to Elevated O3 Concentrations

Abstract: The effects of increasing atmospheric ozone (O3) concentrations on cool-season plant species have been well studied, but little is known about the physiological responses of cool-season turfgrass species such as Lolium perenne and Festuca arundinacea exposed to short-term acute pollution with elevated O3 concentrations (80 ppb and 160 ppb, 9 h d−1) for 14 days, which are widely planted in urban areas of Northern China. The current study aimed to investigate and compare O3 sensitivity and differential changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…At the same time, ROS exposure causes chlorophyll degradation, inhibition of chlorophyll syn thesis enzymes, and other deleterious effects in plants (Asada, 1994;Aarti et al, 2006). In particular, a decrease in the concentration of Chl in plants has been reported under several conditions associated with atmospheric pollution (Thawale et al, 2011;Hariram et al, 2018;Mukherjee et al, 2019;Banerjee et al, 2021), as well as under influence of individual air polluting substances, including SO 2 (Mohasseli et al, 2017;Duan et al, 2019), NO 2 (Yue et al, 2020) and ozone (Singh et al, 2012;Xu et al, 2022).…”
Section: Resultsmentioning
confidence: 98%
“…At the same time, ROS exposure causes chlorophyll degradation, inhibition of chlorophyll syn thesis enzymes, and other deleterious effects in plants (Asada, 1994;Aarti et al, 2006). In particular, a decrease in the concentration of Chl in plants has been reported under several conditions associated with atmospheric pollution (Thawale et al, 2011;Hariram et al, 2018;Mukherjee et al, 2019;Banerjee et al, 2021), as well as under influence of individual air polluting substances, including SO 2 (Mohasseli et al, 2017;Duan et al, 2019), NO 2 (Yue et al, 2020) and ozone (Singh et al, 2012;Xu et al, 2022).…”
Section: Resultsmentioning
confidence: 98%
“…It was found that high temperatures eventually lead to a decrease in the activities of antioxidant enzymes (SOD, POD, and CAT) related to antioxidant metabolism in reproductive organs [32]. The contents of AsA and GSH in leaves of tall fescue and perennial ryegrass decreased under high-temperature stress [33]. The activities of enzymes (APX, DHAR, MDHAR, and GR) related to the AsA-GSH cycle were also affected by high temperatures.…”
Section: Introductionmentioning
confidence: 99%